Obstructive sleep apnea: Clinical and diagnostic features - Sunitha C; Aravindkumar S (Wolters Kluwer Medknow Publications, 2009)
Obstructive sleep apnea (OSA) is an increasingly common disorder. It is characterized by frequent episodes of airway obstruction associated with a reduced caliber of the upper airway and is vulnerable to further narrowing and collapse. Acute and repetitive effects of apnea and hypopnea include oxygen desaturation, reduction in intrathoracic pressure, excessive daytime sleepiness, impaired executive function and central nervous system arousals. The apnea-hypopnea index and respiratory distress index help quantify the severity of the condition. The condition is associated with several clinical symptoms of which daytime sleepiness is considered the cardinal symptom. Obesity is one of the major predisposing factors. Three types of apneas have been recognized -obstructive, central and mixed; OSA is the commonest. This review will cover aspects of their radiologic features, diagnosis and management.